Observation on the Breeding Eurasian Sparrowhawk (Accipiter nisus nisosimilis) in the Tuul River Valley, Mongolia - Ariunbaatar Barkhasbaatar; Gankhuyag Purev-Ochir (Mongolian Journal of Biological Sciences, 2020)
We found a pair of Eurasian sparrowhawk (Accipiter nisus nisosimilis) breeding in the Tuul River valley near Gachuurt Village of Ulaanbaatar city. Three chicks occurred in the nest, which were nearly fully feathered. Based on our estimation, the chicks were about four weeks old and would be leave the nest around 20th July. We, therefore, estimated that the incubation of this pair may have been started around 20th May, and the breeding period of this migratory species in Mongolia may start relatively later than in Europe. According to the historical data, the sparrowhawks prefer to nest on coniferous and deciduous trees in forests, and willow trees along the river basins in Mongolia.